Counterfactual thinking : Study of the focus effect of scenarios and blame ascriptions to victim and perpetrator - Marques, João Amaral (2015)
In two different studies we examined the focus effect of a scenario (i.e., the fact that a given character is the protagonist of a story) on two interconnected domains: the generation of counterfactual thoughts and the ascription of blame. It was hypothesised that being the focal agent of a story would not only lead to more counterfactuals centred on him or her, but also to greater ascriptions of blame as it would be easier to imagine how that actor could have behaved differently had he chosen or wanted to, and thus avoided a deleterious outcome. Different negatively-valenced scenarios depicting a certain misfortune such as a mugging were created in which victim, perpetrator or both characters, were the centre of the story. Results showed that placing either victim or perpetrator as the protagonist of a scenario increases the number of counterfactual thoughts centred on that character, but does not necessarily increase the blame attributed to him or her as the perpetrator was always ascribed more blame than the victim, irrespective of who was the protagonist. Study 2’s findings replicate those of Study 1 even with a different experimental design, modified materials, and various counterbalancing measures, hence suggesting that being the protagonist enables one to easily consider counterfactual alternatives involving that actor, but does not prevent one from identifying who is rightfully to blame for a given misfortune. The results and their implications were interpreted according to different theoretical perspectives and possible future avenues of research are discussed.